2017
DOI: 10.1111/cas.13196
|View full text |Cite
|
Sign up to set email alerts
|

Sox2‐dependent inhibition of p21 is associated with poor prognosis of endometrial cancer

Abstract: Sex‐determining region Y‐box 2 (SOX2) is an essential factor involved in the self‐renewal and pluripotency of embryonic stem cells and has functions in cell survival and progression in many types of cancers. Here, we found that several endometrial cancer cell lines expressed SOX2, which was required for cell growth. Additionally, SOX2 overexpression regulated the expression of cyclin‐dependent kinase inhibitor 1A (CDKN1A), and SOX2 specifically bound to p21 promoter DNA in endometrial cancer cell lines express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 52 publications
1
27
0
Order By: Relevance
“…In addition, immunohistochemical staining for the NUTM1 protein was performed as previously reported 14, 26. Briefly, after deparaffinization, antigen retrieval was performed with Target Retrieval Solution (10 mM citrate buffer, pH 6.0; Dako) in a microwave for 30 minutes at 96°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, immunohistochemical staining for the NUTM1 protein was performed as previously reported 14, 26. Briefly, after deparaffinization, antigen retrieval was performed with Target Retrieval Solution (10 mM citrate buffer, pH 6.0; Dako) in a microwave for 30 minutes at 96°C.…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting experiments for NUTM1 (C52B1, Cell signaling technology; dilution ratio 1:1000) and anti-glyceraldehyde-3-phosphate dehydrogenase (GAPDH) antibody, clone 6C5 (MAB374, Merck Millipore Headquarters; dilution ratio 1:1000) were performed as previously reported. 13,14,26 Tissues were lysed in RIPA buffer (50 mM Tris at pH 8.0, 150 mM NaCl, 1% Nonidet P-40, 0.5% sodium deoxycholate, 0.1% sodium dodecyl sulfate [SDS], and 1 mM EDTA) supplemented with protease inhibitors (Roche). The lysates were separated by SDS-polyacrylamide gel electrophoresis on 5%-20% gradient gels and transferred to polyvinylidene difluoride (PVDF) membranes (Millipore).…”
Section: Western Blottingmentioning
confidence: 99%
“…Pityński et al 15 analyzed expression level of SOX2 in samples from EC patients and found higher expression level of it in high-grade (G3) compared with moderate-grade (G2) and low-grade (G1) of EC. High expression level of SOX2 in tissues was also associated with poorer outcomes of patients with advanced-stage EC 11 . In contrast, Wong et al 58 proposed that SOX2 was a tumor suppressor gene inhibiting the progression of EC, and low level of it was identified as an indicator of type II serous, clear cell adenocarcinoma as well as shorter survival.…”
Section: Sox Genes In Gcsmentioning
confidence: 95%
“…Overexpression of SOX2 in cells promoted cell proliferation by inhibiting expression of p21 11 , while low level of SOX2 in tissues caused by promoter hyper-methylation was conversely accompanied by initiation of EC 58 . These phenomena reflecting the role of SOX2 as a biomarker of clinical features in patients with EC was possibly due to different locations of SOX2 and its currently unclear mechanisms.…”
Section: Sox Genes In Gcsmentioning
confidence: 97%
See 1 more Smart Citation